2022
DOI: 10.1155/2022/1736350
|View full text |Cite|
|
Sign up to set email alerts
|

Recognition of Human Body Feature Changes in Sports Health Based on Deep Learning

Abstract: With the rapid development of social economy and the extensive and in-depth development of national fitness activities, national physical fitness monitoring and research work has achieved rapid development. In recent years, the application of deep learning technology has also achieved research breakthroughs in the field of computer vision. How deep learning technology can effectively capture motion information in sample data and use it to realize the recognition and classification of human actions is currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The technology is still in the development stage. After continuous updating and iteration, the accuracy to evaluate human joints has gradually improved [12]. It is progressively beginning to be applied in sports training, sports function evaluation, sports injury protection, efficacy evaluation, and other fields [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The technology is still in the development stage. After continuous updating and iteration, the accuracy to evaluate human joints has gradually improved [12]. It is progressively beginning to be applied in sports training, sports function evaluation, sports injury protection, efficacy evaluation, and other fields [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%